Primary sciatic nerve lymphoma: a case report and review of the literature. Issue 9 (16th August 2006) - Descamps, M J L; Barrett, L; Groves, M; Yung, L; Birch, R; Murray, N M F; Linch, D C; Lunn, M P T; Reilly, M M
Abstract : A patient with primary B cell non-Hodgkin's lymphoma of the sciatic nerve is described. He presented with neuropathic symptoms in the left leg, initially diagnosed as tarsal tunnel syndrome. Magnetic resonance imaging (MRI) identified the abnormality in the sciatic nerve. A fascicular biopsy of the sciatic nerve showed a diffuse large B cell non-Hodgkin's lymphoma. The patient was treated with chemotherapy and rituximab (anti-CD20 monoclonal antibody). Four months later he was in remission, and remains so 48 months from presentation. Primary lymphoma of single peripheral nerves may be a unique subtype of extranodal lymphoma, which usually follows an aggressive course and has a variable response to current therapeutic strategies. MRI is useful, alongside electrophysiological studies, in patients with atypical peripheral nerve symptoms.